Analisi Penerapan Sistem Informasi Akutansi dan Motivasi Kerja dalam Meningkatkan Kinerja Karyawan Pada PT. Perkebunan Nusantara IV Regional 1 Kebun Sarang Giting - Adelia Marhamah; Yenni Samri Juliati Nasution; Juliana Nasution (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The aim of this research is to find out information systems play an important role in producing information quickly, effectively and efficiently. The main problem in this article is how the implementation of an Accounting Information System improves the performance of employees at PT. PERKEBUNAN NUSANTARA IV REGIONAL I KEBUN SARANG GITING. To obtain materials and data related to this research, research was conducted using descriptive analysis methods, using interview techniques with finance and accounting departments. The conclusion of the research is that the implementation of the accounting information system is in accordance with theory, but it still needs improvements in the procedures carried out. The research results show that the role of work motivation in improving employee performance is: Opportunities for development and growth at work aimed at improving employee performance, improving the quality of employee service, increasing creativity in employee work, increasing employee potential at work.